2018
DOI: 10.2174/1381612824666180607124038
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-based Virtual Screening and Its Applications to Alzheimer’s Drug Discovery: A Review

Abstract: Background: Virtual Screening (VS) has emerged as an important tool in the drug development process, as it conducts efficient in silico searches over millions of compounds, ultimately increas-ing yields of potential drug leads. As a subset of Artificial Intelligence (AI), Machine Learning (ML) is a powerful way of conducting VS for drug leads. ML for VS generally involves assembling a filtered train-ing set of compounds, comprised of known actives and inactives. After training the model, it is validated and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(95 citation statements)
references
References 89 publications
0
94
0
1
Order By: Relevance
“…Agents against targets such as BACE1 and APP amyloidosis have proved to be ineffective against AD progression so far. Therefore, further studies in AD pathogenic mechanisms and future utility of artificial intelligence (AI)-based drug discovery tools may aid in developing novel theranostic agents for AD (140,141).…”
Section: Resultsmentioning
confidence: 99%
“…Agents against targets such as BACE1 and APP amyloidosis have proved to be ineffective against AD progression so far. Therefore, further studies in AD pathogenic mechanisms and future utility of artificial intelligence (AI)-based drug discovery tools may aid in developing novel theranostic agents for AD (140,141).…”
Section: Resultsmentioning
confidence: 99%
“…The prediction that patients with stable MCI will develop AD achieved ROC-AUC of 92.5% [26] , [27] , [28] , [29] . Carpenter and Huang analyzed ML methods (naïve Bayes, kNN, SVM, random forest, and neural networks) for virtual screening (VS) [30] . They presented a workflow for applying ML-based VS to the search for potential therapeutic drugs for AD.…”
Section: Discussionmentioning
confidence: 99%
“…6 This issue, along with the current deluge of structural data, has prompted the use of machine learning methods in structure-based virtual screening and in the verification of docked structures. [7][8][9] Machine learning has found its way into many scientific domains, and drug discovery is no exception (a review can be found in [10]). Multiple machine learning-based virtual screening methods have been developed.…”
Section: Introductionmentioning
confidence: 99%